2008
DOI: 10.1523/jneurosci.4155-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Dendrites of Mammalian Neurons Contain Specialized P-Body-Like Structures That Respond to Neuronal Activation

Abstract: Intracellular mRNA transport and local translation play a key role in neuronal physiology. Translationally repressed mRNAs are transported as a part of ribonucleoprotein (RNP) particles to distant dendritic sites, but the properties of different RNP particles and mechanisms of their repression and transport remain largely unknown. Here, we describe a new class of RNP-particles, the dendritic P-bodylike structures (dlPbodies), which are present in the soma and dendrites of mammalian neurons and have both simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
186
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(200 citation statements)
references
References 47 publications
14
186
0
Order By: Relevance
“…Remarkably, four out of the five proteins colocalized, albeit at different levels, with a YFP-labeled dFMR1 granules in neurites of cultured Drosophila motor neurons ( Figure 2; Barbee et al 2006). No specific antibody was available to test the presence of Dco/Dbt in neuronal granules but studies from Saccharomyces cerevisiae have shown that a homologous protein is present on P bodies (D. Muhlrad and R. Parker, unpublished observations), which contain many of the components found in neuronal granules (Barbee et al 2006;Cougot et al 2008;Miller et al 2009). Thus, we conclude that at least PABP, Orb2, Rm62, and SmD3 are components of FMRP-containing RNA granules found in neuronal processes.…”
Section: Resultsmentioning
confidence: 98%
“…Remarkably, four out of the five proteins colocalized, albeit at different levels, with a YFP-labeled dFMR1 granules in neurites of cultured Drosophila motor neurons ( Figure 2; Barbee et al 2006). No specific antibody was available to test the presence of Dco/Dbt in neuronal granules but studies from Saccharomyces cerevisiae have shown that a homologous protein is present on P bodies (D. Muhlrad and R. Parker, unpublished observations), which contain many of the components found in neuronal granules (Barbee et al 2006;Cougot et al 2008;Miller et al 2009). Thus, we conclude that at least PABP, Orb2, Rm62, and SmD3 are components of FMRP-containing RNA granules found in neuronal processes.…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, BDNF was shown to induce the translocation of dendritic P-body-like structures toward the distal regions of dendrites in hypothalamic neurons (Cougot et al, 2008). These P-body-like structures often contained ZBP1 and FMRP, well described RNA-binding proteins involved in mRNA transport (Cougot et al, 2008). These findings, together with the emerging roles of miRNAs in the regulation of local mRNAs, suggest a close interplay between P-bodies and RNA transport granules.…”
Section: Bdnf Regulation Of P-bodiesmentioning
confidence: 99%
“…It was recently shown that BDNF treatment increased the formation of dendritic and somatic P-bodies that contain untranslated RNA targeted for repression or degradation (Huang et al, 2012). Furthermore, BDNF was shown to induce the translocation of dendritic P-body-like structures toward the distal regions of dendrites in hypothalamic neurons (Cougot et al, 2008). These P-body-like structures often contained ZBP1 and FMRP, well described RNA-binding proteins involved in mRNA transport (Cougot et al, 2008).…”
Section: Bdnf Regulation Of P-bodiesmentioning
confidence: 99%
“…Heterologously expressed EGFP-FMRP has been used as a surrogate marker for endogenous FMRP by several laboratories in a wide variety of studies (Antar et al, 2005;Castren et al, 2001;Cougot et al, 2008;Darnell et al, 2005;Davidovic et al, 2004;De Diego Otero et al, 2002;Dictenberg et al, 2008;Levenga et al, 2009;Pfeiffer and Huber, 2007). Like endogenous FMRP, EGFP-FMRP was found to co-sediment with polyribosomes in cultured neurons (Darnell et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In contradistinction to endogenous FMRP granules, which are small, and while pervasive in cultured cells not particularly prevalent, (Cougot et al, 2008;Dolzhanskaya et al, 2006a;Dolzhanskaya et al, 2006b) EGFP-FMRP granules are large, and amorphous. In fact, they tend to be larger and more non-uniformly round than stress granules, Table 2.…”
Section: Discussionmentioning
confidence: 99%